Use of Electronic Information Resources and Academic Performance of University Teachers: A case study - Sivathaasan, N.; Velnampy, T. (My University, 2013)
Electronic Information Resources (e-resources) play an important role in teaching and learning process at university level and provide superior assistance to its users. The main objective of this study is to identify the impact of usage of e-resources on academic performance of the university teachers. As this study was limited to the university teachers, working at the University of Jaffna, Sri Lanka, Stratified random sampling technique were adopted to select a sample from each of the five different faculties in proportion to the actual size of the group in the total population. The study employs correlation and regression model to test the operational hypotheses and results revealed that usage of e-resources has a strong positive association with academic performance (r = 0.623, p < 0.01). Multiple regression analysis showed that the usage of e-resources has an impact on academic performance at the rate of 38.8 % (R2= 0.388), which is statistically significant at the levels of 0.01 (p < 0.01). This study would absolutely benefit the research scholars through exploring impact of usage of e-resources on academic performance.
Keywords: Electronic Information Resources; Academic Performance; University Teachers.